Strategies for Enhancing Operational Cost Efficiency in Water Treatment Plants through the Integration of Green Concepts and Value Engineering - Hendy Gunawan Putra; Budi Susetyo (Eduvest - Journal of Universal Studies, 2026)
The government prioritizes targets 100% access to drinking water through Vision 2030, with a service coverage target of 94.61% in Tangerang Regency by 2030. Water Treatment Plants (WTPs) are a crucial component of clean water supply systems, yet their operation poses environmental impacts. This research analyzes the operational cost efficiency of WTPs by integrating green concepts and Value Engineering (VE) methods. The aim is to identify economical and environmentally friendly solutions without compromising water quality and quantity, by pinpointing key factors influencing operational cost efficiency. The methodology encompassed literature review, hypothesis formulation, and data collection via questionnaires, analyzed using Structural Equation Modeling (SEM) and VE studies. Results indicate that Sustainable Technology with Renewable Energy Use and Innovation Implementation are the most influential variables. A case study at PERUMDAM TKR WTP applies VE and Life Cycle Cost Analysis (LCCA) for green concept operational cost analysis. VE results in an 8.97% cost increase, amounting to IDR 1,717,378,957. LCCA shows green concept investment in WTPs is viable with NPV > 0 (IDR 14,076,121,227.33), IRR of 16.42%, and a Payback Period of 8.60 years